There has to be a better way: place managers for crime prevention in a surveillance society - Douglas, Stephen (International journal of comparative and applied criminal justice, 2022)
We live in a surveillance society. Often justified under the guise of government anti-terrorism activities, domestic crime reduction, or both, surveillance takes many forms, including closed-circuit television cameras, networked cameras, and facial recognition applications. There is also a range of alternative forms of surveillance, measures considered less of an imposition to privacy, civil liberties, and other personal freedoms. One example is place managers: employees who perform a surveillance function secondary to their employment duties (e.g., bus drivers, parking lot attendants, train conductors). This article reports on an updated systematic review of the effects of place managers on crime in public and private space. Following identification and screening of several hundred references, a total of six studies met the inclusion criteria. Findings indicate that place managers represent a promising situational technique for preventing crime. Future place manager interventions need to be guided by the rich body of theory on place management.